+0  
 
0
34
1
avatar

Let

\(f(x) &= 2x + 5 g(x) &= √{f(x)} - 2 h(x) &= f(g(x)) \)

What is 

\( h(2)\)?

Guest Feb 10, 2018

Best Answer 

 #1
avatar+6365 
+2

 f(x)   =   2x + 5

g(x)   =   √[ f(x) ] - 2

h(x)   =   f(g(x))

 

h(2)   =   f(g(2))

 

g(2)   =   √[ f(2) ] - 2

 

 f(2)   =   2(2) + 5   =   4 + 5   =   9

 

g(2)   =   √[ f(2) ] - 2   =   √[ 9 ] - 2   =   3 - 2   =   1

 

h(2)   =   f(g(2))   =   f( 1 )

 

 f(1)   =   2(1) + 5   =   2 + 5   =   7

 

h(2)   =   f(g(2))   =   f( 1 )   =   7

hectictar  Feb 10, 2018
Sort: 

1+0 Answers

 #1
avatar+6365 
+2
Best Answer

 f(x)   =   2x + 5

g(x)   =   √[ f(x) ] - 2

h(x)   =   f(g(x))

 

h(2)   =   f(g(2))

 

g(2)   =   √[ f(2) ] - 2

 

 f(2)   =   2(2) + 5   =   4 + 5   =   9

 

g(2)   =   √[ f(2) ] - 2   =   √[ 9 ] - 2   =   3 - 2   =   1

 

h(2)   =   f(g(2))   =   f( 1 )

 

 f(1)   =   2(1) + 5   =   2 + 5   =   7

 

h(2)   =   f(g(2))   =   f( 1 )   =   7

hectictar  Feb 10, 2018

14 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details